Scope and cost-effectiveness of fermented corn straw roughage-based buffalo fattening approach - Roy, Biplob Kumer; Huda, Nazmul; Sultana, Nasrin (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This experiment was undertaken to assess the scope and cost-effectiveness of the fermented corn mixture (FCM)-based buffalo fattening approach compared to urea molasses straw (UMS) and silage-based approach. Materials and Methods: A completely comparative randomized design experiment was conducted for 90 days with three treatments and five buffalo bulls in each. UMS, silage, and FCM roughage-based fattening diets were attributed as T1, T2, and T3, respectively. Two types of protein supplements, i.e., Type 1 (Bangladesh Livestock Research Institute-developed) for T1 and T2 and Type 2 (prescribed by farmers) for T3 treatments, were used. All the parameters were analyzed through Statistical Package for the Social Sciences, 20 software. Results: Dry matter intake (kg, %live weight) was significantly higher in T1 (2.65), followed by T2 (2.34) and T3 (2.00), respectively. The crude protein intake, digestible crude protein intake, and digestible dry matter intake (kg/d) significantly (p < 0.05) differed between T1 and T3, but not T2. The digestibility of acid detergent fiber (65.97) was significantly higher for T3 than T1 and T2 (54.44 and 58.73, respectively). Neutral detergent fiber digestibility of T3 (70.35) also differed (p < 0.05) with T1 (60.97) but not T2 (64.78). No difference was observed in the case of growth, but feed conversion ration was found to be significantly (p < 0.05) better in T2 (7.10) than T1 (8.35), where T3 (7.24) was neutral. The significantly (p < 0.001) highest expense [216.37 Bangladesh taka (BDT)/kg gain] was required for T1, followed by T2 and T3 (174.47 and 126.33 BDT/kg gain, respectively). Net profit from T3 and T2 (15,877 and 15,175 BDT, respectively) gained significantly (p < 0.05) higher than T1 (11,265 BDT). Conclusion: The FCM-based diet was suitable and cost-effective as a buffalo fattening approach. J. Adv. Vet. Anim. Res., 8(2): 195-202, June 2021